Seguridad de la infraestructura de la red de datos del GAD Municipal del Cantón Vinces - Escobar Garzón, Lissette Verónica (2019)
The security of information is fundamental for any public entity, since the documentation handled is very important and in certain cases, due to the data of the taxpayers, due to which it is necessary to have all the security measures required by the authorities. international standards to prevent user data from being extracted fraudulently. The Municipal Autonomous Decentralized Government of the Vinces canton is an entity of public law, which exercises the representation of the State in the territory delimited in the canton of Vinces, where the information of all the owners of both urban and rural properties is available, as well as the users of patents or other procedures that are performed, so that to expedite the information of the data has been digitized and stored in computer programs, which is in turn are protected with security protocols to prevent them from being stolen or kidnapping by computer criminals. The research carried out is for the purpose of knowing the different elements that constitute the security of the data network infrastructure of the Municipal GAD of the Vinces canton, where it is intended to know the levels of security that it has within the institution to avoid the loss of valuable information of the taxpayers and internal documents of the entity, as well as the way of distribution of its internal network in all the municipal dependencies, because there are several municipal buildings that are linked to have the Internet service.